PENINGKATAN HASIL BELAJAR PPKn TENTANG POLA HIDUP GOTONG ROYONG MELALUI MODEL KOOPERATIF LEARNING TIPE MAKE A MATCH DI KELAS IV SD INPRES PERUMNAS 2 - Tusi, Josua (Universitas Nusa Cendana, 2024)
The researcher aims to illustrate the utilization of the Make a Match Type Cooperative Learning Model, supported by Card Matching Image Media, to enhance the learning achievements of Grade IV students at SDI Perumnas 2 in understanding the concept of mutual cooperation lifestyle. The research methodology employed is Classroom Action Research, comprising planning, implementation, observation, and reflection stages. The study is conducted at SDI Perumnas 2, involving all Grade IV students as participants. Data gathering is conducted through observation methods and assessments, with qualitative descriptive analysis utilized for data interpretation. The findings from the initial phase of the study indicated an average score of 46.12, which saw improvement following interventions in Cycle I, reaching an average of 65.29. Subsequent actions in Cycle II resulted in a further increase to an average score of 66.93. Notably, there was a consistent rise in the average score from pre-cycle to Cycle I and from Cycle I to Cycle II, amounting to 83.5. Additionally, the percentage of students achieving classical learning proficiency exhibited an upward trend, rising from 31.25% in the pre-cycle to 68.75% in Cycle I and eventually reaching 93.75% in Cycle II. These results suggest that the application of the Make a Match type Cooperative Learning Model, supported by Puzzle Image Media, pertaining to the concept of mutual cooperation lifestyle, has significantly enhanced the learning outcomes of Grade IV students in class IVI at SDI Perumnas 2.